2019
DOI: 10.1080/14664208.2019.1700056
|View full text |Cite
|
Sign up to set email alerts
|

Agency in educational language planning: perspectives from higher education in Tunisia

Abstract: Post-modern approaches to language policy have emphasised the role of agency in implementing and appropriating language policies (Ricento, 2000;Johnson and Johnson, 2015). While agency is often perceived in positive terms, Liddicoat (2019) calls on language policy researchers to investigate its problems and constraints. This article discusses the interplay of structure and agency in educational language policies in Tunisian higher education, a sector characterised by a 'benign neglect' (Piller, 2016) approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Drawing on an ecological perspective of LPP, our study found an array of factors nested in a layered structure that impact the educators' agency, leading them to plan the English LEP and keep it sustainable within the kindergarten. This finding broadly supports prior research, which underlines the complex influence of micro-(i.e., factors within the kindergarten), meso-(i.e., factors within family, community), and macro-level (i.e., cultural ideologies and government policies) factors on local actors' agency in educational settings [27,29,67]. Nevertheless, our study revealed more nuanced evidence of these factors' effects.…”
Section: An Ecosystem Sustaining the Educators' Agency In Micro-lp Th...contrasting
confidence: 51%
“…Drawing on an ecological perspective of LPP, our study found an array of factors nested in a layered structure that impact the educators' agency, leading them to plan the English LEP and keep it sustainable within the kindergarten. This finding broadly supports prior research, which underlines the complex influence of micro-(i.e., factors within the kindergarten), meso-(i.e., factors within family, community), and macro-level (i.e., cultural ideologies and government policies) factors on local actors' agency in educational settings [27,29,67]. Nevertheless, our study revealed more nuanced evidence of these factors' effects.…”
Section: An Ecosystem Sustaining the Educators' Agency In Micro-lp Th...contrasting
confidence: 51%
“…To address the uncertainty concerns raised by the lecturers in this study, it is important for policy makers at different levels, be national or local, to engage with a range of language policy influencers such as teachers, students, parents, employers and educational funding agencies in order to develop a coherent policy that aligns the education system with local and global demands (Badwan, 2019b). As part of these wider national consultations, it is crucial to draw attention to issues of language access, inequality and epistemic injustice and to consider policies that address these challenges in order to produce just arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Should change start with the language of instruction in HE or should it start with employers changing the linguistic expectations they place on university graduates? Due to the lack of coordination between policy influencers, the lecturers expressed a sense of professional anxiety regarding the shift to English (see also Badwan, 2019b).…”
Section: (Interview 1)mentioning
confidence: 99%
“…• first, to study the links between agency and structure (Ahearn, 2001;Johnson & Johnson, 2015;Liddicoat, 2018); • second, to develop a multi-levelled approach to researching language policy and planning (Badwan, 2021;Baldauf, 2006;Bouchard & Glasgow, 2019).…”
Section: Study Parametersmentioning
confidence: 99%